Effect of non-surgical periodontal therapy on concentrations of salivary biomarkers in patients with chronic periodontitis: A clinical trial - Sahar Jabali; Mehran Mesgari Abbasi; Amir Ardalan Abdollahi (Journal of Advanced Periodontology and Implant Dentistry, 2019)
Background. Certain salivary biomarkers that are considered unique in relation to the physiological aspects of periodontitis can be helpful in the diagnosis of periodontitis by considering quantitative changes in such biomarkers. This study was undertaken to answer the question to what extent non-surgical periodontal treatment can affect concentrations of salivary biomarkers in patients suffering from chronic periodontitis. Methods. Eighteen patients with generalized moderate-to-severe chronic periodontitis were recruited for this study by considering periodontal parameters of gingival index (GI), probing pocket depths (PPD), clinical attachment levels (CAL) and a number of radiographic parameters. Salivary samples were analyzed at baseline and at one-month interval after non-surgical periodontal treatment consisting of scaling and root planing. Concentrations of salivary biomarkers, including cortisol, immunoglobulin A (Ig A), IL-6, interferon-γ, soluble intercellular adhesion molecule-1 (sICAM) and ALP, were determined with the use of an ELISA kit. Data were subjected to statistical analyses using paired t-test, with SPSS 15. Statistical significance was set at P<0.05. Results. Mean levels of IgA and interferon-γ decreased significantly after treatment (P<0.05); however, cortisol concentrations increased significantly after treatment. In addition, the decrease in IL-6, sICAM-1 and ALP levels were not significant (P>0.05). Conclusion. The results showed that the salivary levels of IgA and interferon-γ decreased and those of cortisol increased significantly subsequent to scaling and root planing.